Status Kewarganegaraan Etnis Tionghoa Pasca Undang-undang Nomor 12 Tahun 2006 di Kota Medan - Suharyanto, Agung (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik Universitas Medan Area, 2015)
Status is a state or position (person, entity, etc.) to do with the public sekitar. UU 12 2006 that legislation governing citizenship of the Republic of Indonesia. Citizens are people as part of a population that is becoming an element of the state. Citizenship is a membership that shows the relationship between the citizen or bond with other residents. This research aims to determine the citizenship status of ethnic Chinese after the Law No. 12 of 2006 on Citizenship of the Republic of Indonesia and the implementation of Law No. 12 of 2006 on ethnic Chinese. The method used in this research is descriptive quantitative research methods were implemented in the district of Medan Sunggal Medan. Data collection tool used in this study was the observation and dissemination angket. Jumlah population in this study were 285 households and the determined sample is 20% of the total population that is 57 families. After conducting research and data processing can be concluded after the birth or the Law No. 12 of 2006 on Citizenship of the Republic of Indonesia ethnic Chinese community in the Village VII Environmental Lalang Sunggal district of Medan Medan city have Indonesian citizenship status.